Greetings as a Marker of Politeness in Speech for Elementary School Teacher Education Students and the Instilling of Character Values - Setiawan Edi Wibowo (STAI Hubbulwathan Duri, 2023)
This study aims to describe the form of greeting as a lingual marker of language politeness in elementary school teacher education study program students and its relationship to character education. The research methodology employed in this study is a qualitative descriptive approach. The dataset utilised in this research comprises WhatsApp conversations exchanged among students pursuing elementary school teacher education at Yogyakarta State University. These messages are analysed to assess the level of language politeness exhibited. The data sources for this research consisted of students enrolled in the Elementary School Teacher Education programme at Yogyakarta State University. The research employed a documentation-based data collection strategy. The aforementioned approach is employed for the purpose of recording WhatsApp chats within the context of elementary school teacher education students at Yogyakarta State University. The method employs a sophisticated approach involving the processes of recording, listening, and note-taking. The data analysis in this research employs the padan method, supplemented by pertinent theories and the agih method. The present study examines the various types of lingual politeness markers employed by students enrolled in the Elementary School Teacher Education programme at Yogyakarta State University. Specifically, the study focuses on three categories of politeness markers: religious greeting politeness markers, tribal politeness markers, and universal greeting politeness markers. This shows that the results of this study can be used as a basis in the preparation and development of teaching materials in character education.